The Legality of Brushing Practices in the Viewpoint of Consumer Protection Law and Telematics Law - Swarianata, Vifi; Puluhulawa, Jufryanto; Apripari, Apripari; Kaku, Rismanto; Puluhulawa, Irlan (Universitas Negeri Gorontalo, 2023)
Instant profit-making patterns have been established by the current online purchasing and selling practices. For example, brushing is the activity of internet retailers or merchants fabricating favorable reviews or fraudulent endorsements to boost the reputation of their goods or services. When a customer receives a product or service that falls short of their expectations, brushing can be harmful. This study aims to investigate the legality of online buying and selling in Indonesia, specifically the practice of